2023
DOI: 10.1590/1980-549720230008
|View full text |Cite
|
Sign up to set email alerts
|

Intra-urban spatial variability of breast and cervical cancer mortality in the city of São Paulo: analysis of associated factors

Abstract: Objective: To identify spatial variability of mortality from breast and cervical cancer and to assess factors associated in the city of São Paulo. Methods: Between 2009 and 2016, 10,124 deaths from breast cancer and 2,116 deaths from cervical cancer were recorded in the Mortality Information System among women aged 20 years and over. The records were geocoded by address of residence and grouped according to Primary Health Care coverage areas. A spatial regression modeling was put together using the Bayesian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Table 1 provides the main characteristics of each included study, an outline of the individual characteristics of each study population, and the context in which the impact of mobility was studied. Regarding mobility outcomes, 4 studies reported travel distance [ 6 , 7 , 18 , 19 ], 3 studies reported travel time [ 20 22 ], and 7 studies reported any effect measure such as mammograms not performed or effect on access to cancer screening [ 23 29 ]. To facilitate understanding of the results, the following sections are divided into the impact of mobility on BC screening and the impact of mobility on BC treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 provides the main characteristics of each included study, an outline of the individual characteristics of each study population, and the context in which the impact of mobility was studied. Regarding mobility outcomes, 4 studies reported travel distance [ 6 , 7 , 18 , 19 ], 3 studies reported travel time [ 20 22 ], and 7 studies reported any effect measure such as mammograms not performed or effect on access to cancer screening [ 23 29 ]. To facilitate understanding of the results, the following sections are divided into the impact of mobility on BC screening and the impact of mobility on BC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Also in the Northeast of Brazil, de Sousa et al [ 18 ] demonstrated that, despite important data on geographic distance and time to treatment, treatment delay was not linked to geographic barriers but rather to a fragmentation of health services, that is, to a need to shift the points of care from primary to specialized care with a well-defined patient flow. Finally, Aguiar et al [ 22 ] reported that work commutes of 1 to 2 h were negatively associated with BC mortality in the city of São Paulo, Brazil, and that these findings were important to guide cancer prevention policies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations